An Unusual Case of Raghib Defect and Double-Orifice Tricuspid Valve. Issue 2 (March 2018) - Egbe, Alexander C.; Said, Sameh M.; McLeod, Christopher J.; Barbara, David W.; Connolly, Heidi M.
Raghib defect and double-orifice tricuspid valve are two rare congenital heart defects. We report a case of a 42-year-old man with both Raghib defect and DOTV. The patient underwent reroofing of the coronary sinus with an intra-atrial baffle and annuloplasty of the tricuspid and mitral valves via median sternotomy.